The action of Poria cocos polysaccharides against non-alcoholic fatty liver disease: A preliminary study - Rui Zhou; Qinting Chen; Jie Mo; Meizhen Liu; Ka Wu; Chao Guo (Food Hydrocolloids for Health)
Non-alcoholic fatty liver disease (NAFLD) is a significant public health challenge owing to its current prevalence. Basic and clinical evidence indicates that pyroptosis is responsible for the development of NAFLD to non-alcoholic steatohepatitis. Our previous findings suggested that Poria cocos polysaccharides (PCP) exert promising anti-liver injury benefits. However, the anti-NAFLD action of PCP via the modulation of pyroptosis remains untested. In this study, a network pharmacology- and molecular docking-based approach was used to determine the anti-NAFLD activities and mechanisms of PCP prior to in vitro or in vivo. Based on these bioinformatics data, 31 intersecting genes in PCP (483 target genes), NAFLD (1445 target genes), and pyroptosis (905 target genes) were identified via network pharmacology analysis, and a total of 16 key genes in PCP against NAFLD through the modulation of pyroptosis were determined. Further enrichment analysis revealed the detailed anti-NAFLD functions and molecular mechanisms of PCP. Molecular docking simulations were used to identify the spatial binding features between PCP and the target proteins related to pyroptosis. This study determined the pyroptosis-related cluster genes that act with PCP against NAFLD, thereby offering preliminary evidence to support PCP’s potential in treating NAFLD. Additionally, we identified the possible underlying pyroptotic mechanisms for future experimental validations.